Depression after Delivery: Risk Factors, Diagnostic and Therapeutic Considerations - Debra A. Scrandis; Tehmina M. Sheikh; Robina Niazi; Leonardo H. Tonelli; Teodor T. Postolache (The Scientific World Journal)
Postpartum mood disorders can negatively affect women, their offspring, and their families when left untreated. The identification and treatment of postpartum depression remains problematic since health care providers may often not differentiate postpartum blues from depression onset. Recent studies found potentially new risk factors, etiologies, and treatments; thus, possibly improving the untreated postpartum depression rates. This integrated review examined several postpartum psychiatric disorders, postpartum blues, generalized anxiety, obsessive compulsive disorder, post-traumatic stress disorder, and postpartum psychosis for current findings on prevalence, etiologies, risk factors, and postpartum depression treatments.